ELISA IgG versus CMIA IgG for detection of SARS-CoV-2-specific antibodies in COVID-19 patients - Pathum Sookaromdee; Viroj Wiwanitkit (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
COVID-19 is an important coronavirus infection. The detection of SARS-CoV-2-specific antibodies is important in laboratory medicine. Several serological tests are available. Some serological tests such as ELISA IgG versus CMIA IgG are used as standard references for rapid diagnostic immunoassay. Here, the authors reappraised on the diagnostic property of ELISA IgG versus CMIA IgG for the detection of SARS-CoV-2-specific antibodies in COVID-19 patients. According to the analysis, CMIA IgG has a higher sensitivity and ELISA IgG has a higher specificity. Therefore, CMIA IgG is more appropriate for screening purpose.